Pengaruh Latihan Yoga terhadap Kadar Gula Darah Pasien Diabetes Melitus Tipe 2 : Effect of Yoga Exercise on Blood Sugar Levels of Diabetes Patients Mellitus Type 2 - Leni Merdawati; Reni Prima Gusty; Rika Fatmadona; Esi Afrianti (Fakultas Keperawatan Universitas Andalas, 2018)
The International Diabetes Federation (IDF) states that more than 371 million people in the world aged 20 79 years have diabetes mellitus (DM). While Indonesia is the 7th country with the highest prevalence of diabetes, in the world. Diabetes mellitus has become a widespread epidemic, primarily because of the increasing prevalence and incidence of type 2 diabetes. DM can increase of the morbidity and mortality associated with cardiovascular disease, blindness, kidney disorders, neurological disorders and amputation. Physical activity such as yoga is a key element in the prevention and management of type 2 diabetes, The purpose of this study was to identify the effectiveness of Yoga exercise on decreasing blood sugar levels in Type 2 DM patients. This study used an experimental approach with non equivalent group comparison pre and post test design. The study subjects consist of 40 patients as experimental group and 40 patients as control group. All patient in experimental group were guided by yoga expert for reguler practice with supervision for 3 days. The result of this study show average of blood glucose level in experimental group was 217.05mg/dl with deviation standart 56,735mg/dl, while in the control group was 256.85mg/dl with deviation standart 34.04mg/dl. There was highly significant differences blood glucose average between experimental and control group (p=0,000). Yoga exercise is effective in reducing the blood glucose level on type 2 DM Patients and higly recommended as one of treatment for promotive care.